WHERE ARE THE LIBRARY AND INFORMATION PROFESSIONALS IN E-LEARNING - Banek Zorica, Mihaela; Špiranec, Sonja; Zauder, Krešimir (2007)
Advancement of ICT has influenced all aspects of human life and thereby stimulated changes in educational environment. Academic libraries as a vital part of the traditional educational environment are forced to reply to the new challenges and user demands concerning shifts in educational paradigm and learning environments. Traditional library knowledge has to be adapted to this new environment and new skills have to be learned and developed. Collaboration between teachers and librarians is now crucial if we want to provide students with the quality education according to the guidelines proscribed by the Bologna process and demanded by the contemporary society. In order for these transformation to be fully implemented we have to educate and prepare future Library and information professionals to be confident in using technologies like social and collaborative software, web2.0, and have necessary skills to actively participate in university virtual learning environment as well as to continually develop themselves professionally.
Projekt MZOS
ENG